Impossible creatures - Rundell, Katherine (Impossible creatures, 2024)
Christopher discovers the Archipelago, a world where mythological creatures were secreted away by magic long ago, but those creatures are now dying, and it is up to Christopher and Mal, a girl from the Archipelago, to save both of their worlds.